Overexpression of HIF-2α, TWIST, and CXCR4 Is Associated with Lymph Node Metastasis in Papillary Thyroid Carcinoma - Ni Wang; Hao-Jun Luo; Guo-Bing Yin; Chao-Ran Dong; Man Xu; George G. Chen; Zhi-Min Liu (Clinical and Developmental Immunology)
This study aimed to examine HIF-2α, TWIST, and CXCR4 expression in papillary thyroid carcinoma (PTC) and assesses the association of their expression with clinicopathological indicators. HIF-2α, TWIST, and CXCR4 protein expression in 129 PTCs, 61 nodular hyperplasia, and 118 normal thyroid tissue specimens was analyzed using immunohistochemistry. The protein expression levels of these three molecules were upregulated in PTCs. High protein expression of HIF-2α, TWIST, and CXCR4 was significantly correlated with lymph node metastasis (LNM) (P<0.001). Furthermore, HIF-2α, TWIST, and CXCR4 protein expression was correlated with one another. Concomitant high expression of these molecules had stronger correlation with LNM than did each alone (P=0.032 for HIF-2α/TWIST, P<0.001 for HIF-2α/CXCR4, P=0.018 for TWIST/CXCR4, and P<0.001 for HIF-2α/TWIST/CXCR4). Additionally, HIF-2α, TWIST, and CXCR4 mRNA expression were assessed in 30 PTCs, 10 nodular hyperplasia, and 10 normal thyroid tissue specimens using real-time RT-PCR. TWIST and CXCR4 mRNA expression levels were up-regulated in PTCs, and high mRNA expression of TWIST and CXCR4 was significantly correlated with LNM (P=0.005 and P=0.010, resp.). These results demonstrated that the evaluation of HIF-2α, TWIST, and CXCR4 expression in PTC may be useful in predicting the risk of LNM.